2022
DOI: 10.1213/xaa.0000000000001646
|View full text |Cite
|
Sign up to set email alerts
|

A Remimazolam and Remifentanil Anesthetic for a Pediatric Patient With a Medium-Chain Acyl-CoA Dehydrogenase Deficiency: A Case Report

Abstract: Medium-chain acyl-CoA dehydrogenase (MCAD) deficiency is one of the most common fatty acid oxidation disorders. The choice of anesthetics and blood glucose management are crucial to prevent metabolic decompensation. A 5-year-old Japanese boy with MCAD deficiency was scheduled to undergo surgery for an inguinal hernia. Glucose was continuously infused perioperatively, and his glucose concentrations were within the normal range. Anesthesia was induced and maintained with remimazolam, remifentanil, and intermitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Without pediatric approval, the off-label use of remimazolam for general anesthesia has been limited to published accounts of case reports and small series [ 4 , 5 , 6 , 7 , 16 ]. At our institution, remimazolam has been approved for routine pediatric anesthesia use since 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without pediatric approval, the off-label use of remimazolam for general anesthesia has been limited to published accounts of case reports and small series [ 4 , 5 , 6 , 7 , 16 ]. At our institution, remimazolam has been approved for routine pediatric anesthesia use since 2020.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are no published pediatric studies that report a broad experience with remimazolam when administered as part of a general anesthetic. With only approval for adult administration, the off-label experience in the pediatric population has been limited to case reports only [ 4 , 5 , 6 , 7 ]. At our hospital, remimazolam is approved for off-label use as an adjunct to general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of adults have shown that remimazolam and its antagonist flumazenil have no significant effects on fatty acid metabolism and are good options for anesthesia management in children with muscular dystrophy and medium-chain acyl-CoA dehydrogenase (MCAD) deficiency. [30][31][32] In conclusion, remimazolam is suitable for patients who need MEP monitoring and avoid inhaled anaesthetics.…”
Section: Current Status Of Applications Of Remimazolam General Anesth...mentioning
confidence: 93%
“…Flumazenil can quickly reverse the hypnotic effect of remimazolam, shorten the postoperative extubation time in children, allow spontaneous breathing after failed intubation and avoid delayed awakening in children with congenital metabolic diseases, which improves the safety and controllability of remimazolam anesthesia. 32 , 37 , 41 The FDA-approved doses of remimazolam for benzodiazepine reversal when used for pediatric patients (children 1 year and older and adolescents) receiving conscious sedation or general anesthesia are the initial dose of 0.01 mg/kg given over 15 seconds (up to a maximum dose of 0.2 mg). If no desired return of consciousness is noted after 45 seconds, repeat 0.01 mg/kg (up to 0.2 mg) at 1-minute intervals as needed.…”
Section: Current Status Of Applications Of Remimazolammentioning
confidence: 99%
See 1 more Smart Citation